Dance and mediality: for an ontological and ethical discussion of the performative body - Barros, Né (2017)
From the late nineteenth century we can see at least two major changes in the poetic positions in dance thus pose major challenges to philosophical and aesthetic thought about this art. The first change could be identified as a break with a legacy, a coincidental break with all the steps done by western modern dance and in particular the US. The second change could be identified with the expansion of the frontiers of dance, which includes the whole process of blurring of artistic discipline and artistic genre. The rupture and expansion are, therefore, noteworthy changes that can also be classified in post metaphysical thought. This expanded and inclusive domain of the other can still be thought through a techné not to be confused with ingenuity or the mere ability to artificer, or as an alienating eros, but as the field of performativity as permition for play and disempowerment (questioned authorship in comparison with the other), becoming therefore no man’s land. In this open and undefined field, the dancing body reveals itself as the political and ethical stage par excellence (performance) and an ontological space (performativity). This is the scope of our discussion that finds in mediality the common domain of these two approaches to dance.